Red Bird danced - Quigley, Dawn (Heartdrum, an imprint of HarperCollinsPublishers, 2024)
"Ariel and Tomah have lived in the city's intertribal housing complex all their lives. But for both of them, this Dagwaagin (Autumn) season is different than any before. From his bench outside the front door of his building, Tomah watches his community move around him. He is better at making people laugh than he is at schoolwork, but often it feels like his neighbor Ariel is the only one who really sees him, even in her sadness. Ariel has always danced ballet because of her Auntie Bineshiinh and loves the way dance makes her feet hover above the ground like a bird. But ever since Auntie went missing, Ariel's dancing doesn't feel like flying. As the seasons change and the cold of winter gives way to spring's promise, Ariel and Tomah begin to change too as they learn to share the rhythms and stories they carry within themselves. Dawn Quigley (Ojibwe) tells the story of urban Native kids who find strength in connection with those who came before and in the hope that lets them take flight"--Provided by publisher.